2020
DOI: 10.1111/ajco.13371
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy of lanreotide autogel in Japanese patients with neuroendocrine tumors: Final results of a phase II open‐label extension study

Abstract: Aim:The aim of this study was to describe the long-term safety and efficacy of lanreotide in Japanese patients with neuroendocrine tumors. Methods: The final analyses of a 48-week open-label phase II study (n = 32) and its extension study (n = 17) were conducted. Patients received 4-weekly subcutaneous injections of lanreotide autogel 120 mg. Safety was evaluated by adverse events. Efficacy endpoints included tumor response by RECIST and change in tumor size. Post hoc analyses including tumor growth rate were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…TGR, a predictive marker for progression and survival, is useful for assessing slow-growing tumors like NETs and it has previously been shown that LAN significantly decreased TGR in patients with GEP-NETs (Dromain et al, 2021). Patients' health-related quality of life did not deteriorate during treatment in the present study, and LAN was well tolerated, having a safety profile consistent with that well established in NETs (Bianchi et al, 2011, Caplin et al, 2014, Godara et al, 2019, Ito et al, 2021, Martín-Richard et al, 2013, Michael et al, 2017, Rinke et al, 2021.…”
Section: Discussionsupporting
confidence: 76%
“…TGR, a predictive marker for progression and survival, is useful for assessing slow-growing tumors like NETs and it has previously been shown that LAN significantly decreased TGR in patients with GEP-NETs (Dromain et al, 2021). Patients' health-related quality of life did not deteriorate during treatment in the present study, and LAN was well tolerated, having a safety profile consistent with that well established in NETs (Bianchi et al, 2011, Caplin et al, 2014, Godara et al, 2019, Ito et al, 2021, Martín-Richard et al, 2013, Michael et al, 2017, Rinke et al, 2021.…”
Section: Discussionsupporting
confidence: 76%
“…Presently RLT is recommended by majority of endocrine/oncological societies as a second line of treatment, when progression during somatostatin analogues is noted [ 2 ]. Both lanreotide and octreotide confirmed its efficiency versus placebo in NENs treatment, but long-term effectiveness of this drugs is questionable [ 28 , 29 , 30 ]. Other used ways of treatment are inhibitors of mammalian target of rapamycin (mTORi) like everolimus, ultrasound-guided-radioablation of tumor, or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al. ( 21 ) reported that long-term safety and efficacy of lanreotide was confirmed by phase II open-label extension study in Japanese patients.…”
Section: Standard and Promising Therapies For Unresectable/recurrent Gep-nets And Necsmentioning
confidence: 94%